European Copernicus Services to Inform on Sea-Level Rise Adaptation: Current Status and Perspectives - Melet, Angélique; Buontempo, Carlo; Mattiuzzi, Matteo; Salamon, Peter; Bahurel, Pierre; Breyiannis, George; Burgess, Samantha; Crosnier, Laurence; Le Traon, Pierre-Yves; Mentaschi, Lorenzo; Nicolas, Julien; Solari, Lorenzo; et al. (Frontiers in Marine Science, 2021)
Sea-level rise is a direct consequence of climate change. Primarily due to ocean thermal expansion and transfer from land ice (glaciers, ice sheets) to the ocean, sea-level rise is therefore an integrated indicator of climate change. Coastal zones and communities are expected to be increasingly threatened by sea level changes, with various adverse and widespread impacts. The European Union’s Earth Observation Programme, Copernicus, monitors our planet and its environment, for the ultimate benefit of society. This includes the monitoring of sea level changes and the provision of ancillary fields needed to assess sea-level rise coastal risks, to guide adaptation and to support related policies and directives. Copernicus is organized with a space component, including dedicated Earth Observation satellites (Sentinel missions), and services, which transform the wealth of satellite, in situ and integrated numerical model information into added-value datasets and information usable by scientists, managers and decision-makers, and the wider public. Here, an overview of the Copernicus products and services to inform on sea level rise adaptation is provided. Perspectives from Copernicus services on future evolutions to better inform on coastal sea level rise, associated risks, and support adaptation are also discussed.